Hearts Exposed - Nathoo, A. author. aut Link
XV, 262 p. 29 illus.
Keywords: This book examines the relationship between medicine and the media in 1960's Britain, when the first wave of heart transplants were as much media as medical events and marked a decisive period in post-war history. Public trust in their doctors was significantly undermined, and medicine was held publicly to account as never before.